Lumbar spondylosis: Does conventional X-ray still play the role? - Yus, Teuku M.; Zakaria, Iskandar; Satria, Darma; Illahi, Resti (School of Medicine, Universitas Syiah Kuala, 2024)
Lumbar spondylosis is a very common complaint of severe low back pain (LBP) or lumbar disc herniation and patients often diagnosed by using radiological examination. Lumbar spondylosis is a degenerative process of the spine, but it can also result from various factors. It is often misdiagnosed as a degenerative process because it only involves the corpus vertebra, intervertebral disc, and osteoporosis of the spine. However, many other causes can lead to inappropriate treatment plans. The X-ray is believed to be a helpful tool in the initial imaging test of lumbar spondylosis diagnosis. However, further imaging tests with magnetic resonance imaging (MRI) or computed tomography (CT) scan are highly recommended. This should be noted by physicians working in rural primary and secondary healthcare facilities who might only have the X-ray to make a diagnosis of lumbar spondylosis. This article reviewed published articles on comparing X-ray, CT scan, and MRI diagnosis data of patients with lumbar spondylosis. The analysis provides insight into the role of X-ray in diagnosing lumbar spondylosis.